2017
DOI: 10.18632/oncotarget.16255
|View full text |Cite
|
Sign up to set email alerts
|

Anti-helminthic niclosamide inhibits Ras-driven oncogenic transformation via activation of GSK-3

Abstract: Despite the importance of Ras oncogenes as a therapeutic target in human cancer, their ‘undruggable’ tertiary structures limit the effectiveness of anti-Ras drugs. Canonical Wnt signaling contributes to Ras activity by glycogen synthase kinase 3 (GSK-3)-dependent phosphorylation at the C-terminus and subsequent degradation. In the accompanying report, we show that the anti-helminthic niclosamide directly binds to GSK-3 and inhibits Axin functions in colon cancer cells, with reversion of Snail-mediated epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…Many studies have reported on the niclosamide enhances cytotoxicity on various cancers, including oral cancer, lung cancer, colon, thyroid, cervix, ovarian, kidney, and prostate cancers, via STAT3, EGFR/PI3K/Akt, RANKL Wnt, mTOR, HIF‐1α/VEGF, Ras, c‐myc, and Notch signal pathways and mitochondria dysfunction 11, 12, 13, 14, 26, 27, 28, 29, 30, 31, 32, 33. Cancer cell upregulates other important downstream genes such as STAT3, which contributes to cell proliferation, cell survival, and angiogenesis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on the niclosamide enhances cytotoxicity on various cancers, including oral cancer, lung cancer, colon, thyroid, cervix, ovarian, kidney, and prostate cancers, via STAT3, EGFR/PI3K/Akt, RANKL Wnt, mTOR, HIF‐1α/VEGF, Ras, c‐myc, and Notch signal pathways and mitochondria dysfunction 11, 12, 13, 14, 26, 27, 28, 29, 30, 31, 32, 33. Cancer cell upregulates other important downstream genes such as STAT3, which contributes to cell proliferation, cell survival, and angiogenesis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Other specific GSK3β inhibitors include the small chemicals TDZD8 (4-benzyl-2-methyl-1,2,4-thiadiazolidine-3,5-dione) and TWS119 (4,6-disubstituted pyrrolopyrimidine) and the peptide L803-mts [N-myristol-GKEAPPAPPQS(p)P] (65). In addition, niclosamide, a U.S. Food and Drug Administration approved salicyclamide derivative anthelmintic drug used for the treatment of tapeworm infections, binds to GSK3β and inhibits WNT pathway functions (66). DIF [1-(3-chloro-2,6-dihydroxy-4-methoxyphenyl)hexan-1-one], a putative morphogen produced by Dictyostelium discoideum, suppresses the WNT/β-catenin signaling pathway via the activation of GSK3β and subsequently reduces the expression levels of c-Myc and cyclin D1 (67).…”
Section: Gsk3β Modulators [Prodigiosin Tdzd8 T Ws119 L803-mts Tidmentioning
confidence: 99%
“…Other studies reported the crosstalk between Wnt/β-catenin and Ras-Erk pathways in the colorectal tumorigenesis [54,55]. Wnt signaling is involved in the stability of Ras through regulation of glycogen synthase kinas 3β-mediated Ras phosphorylation [56]. In hepatocellular carcinoma, Wnt signaling modulates lipid homeostasis in a Ras-dependent manner [57].…”
Section: Discussionmentioning
confidence: 98%